Current Overview of Scientific Production Associated with Governance in University: A Bibliometric Analysis - Martínez, Edgar German; Sánchez Vázquez, Elizabeth; Poveda Aguja, Fernando Augusto; Barbosa Guerrero, Lugo Manuel; Cruz Mican, Edgar Olmedo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The main objective of this research is to identify the current panorama of scientific production associated with governance in university institutions. A bibliometric analysis was developed in Scopus using R Core Team 2022-Bibliometrix and Vosviewer software. The results highlight the countries with the highest productivity in the topic of study, with the most representative authors favoring the understanding of governance. The main thematic clusters stand out. It recognizes the role of university governance and its migration to direct spaces and the transition from a face-to-face model.